A house for Hermit Crab - Carle, Eric (New York Aladdin Paperbacks, 2002)
A hermit crab who has outgrown his old shell moves into a new one, which he decorates and enhances with the various sea creatures he meets in his travels.
"Ages 5-8."
Keywords: Hermit crabs -- Fiction; Crabs -- Fiction; Marine animals -- Fiction; Dwellings -- Fiction